Pembuatan Kliping dan Penyusunan Indeks Beranotasi Artikel Rubrik â€œMinang Saisuakâ€ dalam Koran Singgalang Tahun 2017 - Rizky, Muhammad; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
Abstract Â This article is about making index with annotation an articles on the rubric of â€œMinang Saisuakâ€ at Singgalang newspaper 2017. The method used is descriptive method which is described what they are. The data has been collected through direct observation at Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat. The purpose of this article are: (1) to describe making index with annotation an articles on the rubric of â€œMinang Saisuakâ€ at Singgalang newspaper; (2) to describe obstacle and solution of making index with annotation on the rubric of â€œMinang Saisuakâ€ at Singgalang newspaper 2017. Based on the process of making index with annotation which got an articles at Badan Perpustakaan dan Kearsipan Provinsi Sumatera Barat there are 47 articles on the rubric of â€œMinang Saisuakâ€. All article has been copied and making a clipping in paper. The composing index with annotation an articles on the rubric of â€œMinang Saisuakâ€ at Singgalang newspaper has some process. First make certain about newspaper that would like to choose and this article writer choosed Singgalang newspaper; second making clipping all articles on the rubric of â€œMinang Saisuakâ€; composing of index; ordinance of author all articles; ordinance of title all articles; making annotation all articles; and act of determining of keyword.Keywords: index; articels; Minangkabau